Communities of Practice in Academic Administration : An Example from Managing Undergraduate Research at a Research-Intensive University - Pierszalowski, Sophie; James, Gabs; Fetherstonhaugh, Grace; Cheung , Itchung; Chappell , Patrick; Engels , Jennifer; Plaza , Dwaine; Ramos , Stephanie; López-Cevallos , Daniel (Experiential Learning and Teaching in Higher Education, 2022)
None provided